Larvicidal efficacy of silk sericin-capped silver nano bioinsecticides (SS-AgNBIs) against Aedes aegypti - Muniba Tariq; Hafiz Muhammad Tahir; Aamir Ali; Dilawar Abbas; Samima Asad Butt; Mostafa A. Abdel-Maksoud; Fahd A. Al-Mekhlafi (Scientific Reports)
Abstract Dengue, a mosquito-borne disease, is prevalent in tropical and subtropical areas. Nanotechnology has paved new ways for combating insects. Therefore, the current study was planned to evaluate the larvicidal efficacy of silver nano-bioinsecticides against the dengue vector Aedes aegypti. The plant extracts of Psidium guajava (Guava), Calendula officinalis (Marigold) and Ocimum tenuiflorum (Tulsi) were prepared and their component analysis was conducted by GC-MS analysis. Plant extracts conjugated silver nano-bioinsecticides (AgNBIs) were prepared and capped with silk sericin. The larvicidal activities of silk sericin-capped silver nano bioinsecticides (SS-AgNBIs) were evaluated against 4th instar of Ae. aegypti larvae. The formation of silk sericin-capped silver nano bioinsecticides (SS-AgNBIs) was confirmed through UV-analysis, Fourier-transform infrared analysis (FTIR) and Scanning Electron Microscope (SEM). The results of our study indicated that the SS-AgNBIs showed significant toxicity against Ae. aegypti larvae as compared to negative control There was a significant difference (P < 0.001) in the larvicidal potential of the silk sericin capped silver nanobioinsecticides synthesized by tulsi (SS-AgNBI-tenuiflorum), guava (SS-AgNBI-guajava) and marigold (SS-AgNBI-officinalis) against Ae. aegypti larvae. The most effective larvicide was SS-AgNBI-officinalis (LC90: 478), followed by SS-AgNBI-tenuiflorum (LC90: 609 ppm) and SS-AgNBI-guajava (LC90: 1177 ppm) leaf extracts. It is concluded that SS-AgNBI-officinalis and SS-AgNBI-tenuiflorum were stable and exhibited significant larvicidal activities against dengue vector Aedes aegypti, indicating their potential as effective and eco-friendly alternative for vector control in integrated mosquito management programs.